Analisa Performansi Beberapa Metode Kontroler PID Pada Magnetic Ball - Tamaji Tamaji; Yoga Alif Kurnia Utama; Adrianus Raffel (Universitas Islam Lamongan, 2021)
PID controller is a controller that is still widely used in the industrial world. ThePID controller is proven to provide good control performance even though ithas a simple and easy-to-understand algorithm. The important thing in thedesign of this PID controller is to determine the controller parameters or tuning. Project tries to implement advanced PID tuning which involves several tuning methods to get the best performance on a system or plant that is unstable or critically stable, such as controlling the height of a magnetic ball. Some of the methods that will be discussed here are Ziegler-Nichols, Non-control, On Off, Trial Error, and Chien-Hrones-Reswick (C-H-R). From results show that of the five PID Control methods to control the position of the magnetic ball, the best sequential control method is PID Control Trial Error, PID Control On Off, PID Ziegler-Nichols, Chien-Hrones-Reswick Method, and PID Non-Control